ANALISIS DEIKSIS PADA FILM TOBA DREAMS: KAJIAN PRAGMATIK - Rodearthani Br Girsang; I Nyoman Adi Susrawan; Ni Luh Sukanadi (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2023)
The aims of this study were: (1) to find out the forms of deixis and (2) the function of deixis in the Toba Dreams film. This type of research used a qualitative descriptive approach by means of descriptive writing. The data collection method was carried out by observing, documenting, observing and taking notes. While the data analysis method used in this study is the Analysis Interactive Model from Miles and Huberman, which divides the steps in data analysis activities into several parts, namely data collection, data reduction, data presentation, and drawing conclusions or data verification. The results of this study show that basically (1) the forms of deixis found in the Toba Dreams film are persona, time, place, discourse and social deixis. Of the five forms of deixis found, the deixis that appears the most in the Toba Dreams film is the use of deixis persona. (2) The function of deixis in Toba dreams, persona deixis functions as personal pronouns. Time deixis functions as a pronoun that refers to when the utterance is spoken. Place deixis functions as a pronoun. Discourse deixis functions as a pronoun in discourse. And social deixis functions as a pronoun as a reference to the social status that exists in society. The conclusion of this study is that five forms of deixis are determined, namely persona, time, place, discourse and social deixis which function as pronouns or references to personal pronouns. , place pronouns, time pronouns, discourse pronouns and social status pronouns.